Studi Kasus Penerapan Pijat Bayi terhadap Perubahan Tidur dan Menyusu pada Bayi - Sanjaya, Riona; Komalasari , Komalasari; Puspitasari , Angelia; Ainasari, Ainasari (Penerbit Goodwood, 2023)
Purpose: The purpose of this study was to determine the effect of infant massage on the quality of sleep and breastfeeding in infants. because infancy is a golden period or golden age because this period takes place quickly and cannot be repeated. This period is also known as a critical period, which requires adequate nutrition and stimulation to support optimal development and growth. The sensation of touch is very important early in a baby's life to adapt to its environment. Touch stimulation in infants influences positive psychosocial development. One-touch stimulation that can be given to babies is baby massage Research Methodology: This research is a case study with the subject of three infants aged less than 2 months. Result/findings: The results showed that there was a positive change in the duration of sleep and breastfeeding in infants after being given baby massage treatments. It is hoped that health workers, especially midwives, can provide education to parents regarding baby massage as a form of stimulation that parents can do at home.